The prevalence, preventive measures and economic impact of pandemic COVID-19 in India: the initial phase - Ganguly, Arindam; Konar, Ujjal; Kundu, Animesh; Ghosh, Subhadeep; Chatterjee, Ishita; Nad, Susmita; Chatterjee, Sandeep; Nandi, Sristishil; Singha, Sourav; Kali, Sukhen (Acta Biologica Szegediensis, 2020)
The novel coronavirus (SARS-CoV-2) is posing a serious threat to the mankind with its massive infection rate and potentially fatality. A total of 212 countries have been infected within the 112 days of ﬁrst report causing 2 314 621 conﬁrmed cases and 157 847 deaths worldwide. India, the country which is already battling with poverty, malnutrition and high population density is also at the second stage of coronavirus transmission. The situation is worsening and the attention has focused on the prevalence and preventive measures to be taken to protect 1.35 billion people of the largest democratic country of the world. In this review, a study has been designed to evaluate the prevalence, transmission, clinical symptoms, and preventive measures to control the community transmission of this fatal disease. The initial impact of coronavirus disease (COVID-19) outbreak on Indian economy has also been dealt with. This study reviews and summarizes the main points of the epidemic in India until the end of April 2020.